2015
DOI: 10.1136/jmedgenet-2015-103027
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function de novo mutations play an important role in severe human neural tube defects

Abstract: Background Neural tube defects (NTDs) are very common and severe birth defects that are caused by failure of neural tube closure and that have a complex aetiology. Anencephaly and spina bifida are severe NTDs that affect reproductive fitness and suggest a role for de novo mutations (DNMs) in their aetiology. Methods We used whole-exome sequencing in 43 sporadic cases affected with myelomeningocele or anencephaly and their unaffected parents to identify DNMs in their exomes. Results We identified 42 coding DNMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 22 publications
1
77
0
Order By: Relevance
“… Few human reports of Spina bifida; Synophrys, cleft lip and cryptochidism; Anal Atresia; Choroidal Melanoma; Unilateral renal agenesis; congenital cataracts. In mice, PAX3 mutations induce pigment defects, spina bifida, and heart defects (Truncus arteriosus) …”
Section: Piebaldism and Waardenburg Syndromementioning
confidence: 99%
“… Few human reports of Spina bifida; Synophrys, cleft lip and cryptochidism; Anal Atresia; Choroidal Melanoma; Unilateral renal agenesis; congenital cataracts. In mice, PAX3 mutations induce pigment defects, spina bifida, and heart defects (Truncus arteriosus) …”
Section: Piebaldism and Waardenburg Syndromementioning
confidence: 99%
“…For instance, of four genes with loss-of-function mutations associated with human anencephaly, three were differentially expressed in our screen (Lemay et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, de novo LoF mutations in SHROOM3 were experimentally associated with the development of NTDs, suggesting that these variants may also contribute to the genetic etiology of severe human NTDs (Lemay et al 2015). However, the genetic contributions of other SHROOM family members to human NTDs have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and human NTD cohort studies have made it clear that SHROOM3 is involved in NTD etiology (Haigo et al 2003; Hildebrand and Soriano 1999; Lemay et al 2015). The importance of SHROOM3 in NTC is beyond dispute, and a recent study identified two protein truncating de novo mutations in SHROOM3 in human NTD patients (Lemay et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation